Immobilization of invertase and glucose oxidase in conducting copolymers of thiophene functionalized poly(vinyl alcohol) with pyrrole - Yagci, Y.; Toppare, L.; Sahmetlioglu, Ertuğrul; Yuruk, H.; Cianga, Ioan (Elsevier BV, 2006)
Abstract In this study, immobilizations of invertase and glucose oxidase were achieved in conducting thiophene functionalized copolymers of vinyl alcohol with thiophene side groups and pyrrole (PVATh/PPy) via electrochemical polymerization. The kinetic parameters, Vmax (maximum reaction rate) and Km (substrate affinity), of both free and immobilized enzymes were determined. The effect of supporting electrolytes, p-toluene sulfonic acid and sodium dodecyl sulfate, on the enzyme activity and film morphologies was examined. The optimum temperature, operational and storage stabilities of immobilized enzymes were determined. PVATh/PPy copolymer was found to exhibit significantly enhanced properties compared to pristine polypyrrole.
Keywords: immobilization; electropolymerization; glucose oxidase; invertase; poly(vinyl alcohol)